Prenatal assessment of placenta accreta spectrum disorders from ultrasound images using deep learning - Qi, H (2019)
This thesis addresses the task of developing deep-learning-based tools for assessing placenta accreta spectrum disorders (PASD), a series of placental abnormalities that drastically affect maternal health, on placental ultrasound scans obtained from prenatal examinations.